Survey and analysis the critical success factors in the reverse flow inventory management process for returnable packaging - Silva, Wesley Douglas Oliveira; Fontana, Marcele Elisa (Brazilian Journal of Operations & Production Management, 2020)
Goal: This study aimed to propose a procedure to survey of the Critical success Factors (CSF) in the reverse flow inventory management. Design/Methodology/Approach: A problem structuring method (PSM) combined with an approach for analysis of strategic map were used to facilitate and share information in a participatory process, considering all the stakeholder’s perspectives in order to identify and analyse the CSF. A case study of returnable packaging in the metallurgy and steel industry was conducted to validate the proposal. Results: The proposal was able to minimize conflicts and it facilitated the discussions on the CFSs surveyed. In addition, the decision makers have confirmed that their viewpoints were well represented in the strategic map, and they will use the CFS to evaluate the operations performance. Limitations of the investigation: Although the surveyed CSFs are specific to the presented case study, the procedure may be replicated in other organizations to identify their own CSF. Practical implications: The adequate survey of CSFs is fundamental because they have potential to explain the success or failure of a company, since CSFs impact directly on profits, processes performance and competitive environment. Originality/Value: The main contribution was to propose a methodology to survey critical success factors in the reverse flow environment adequate to messy, complex and unstructured situations, as well as this methodology was able to make a cyclic analysis and comprehension of the multiple perspectives, important in group decision maker environments.